2014
DOI: 10.1111/oik.00956
|View full text |Cite
|
Sign up to set email alerts
|

Allocation tradeoffs and life histories: a conceptual and graphical framework

Abstract: Tradeoffs – negative reciprocal causal relationships in net benefits between trait magnitudes – have not always been studied in depth appropriate to their central role in life‐history analysis. Here we focus on allocation tradeoffs, in which acquisition of a limiting resource requires allocation of resource to alternative traits. We identify the components of this allocation process and emphasize the importance of quantifying them. We then propose categorizing allocation tradeoffs into linear, concave and conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…In contrast, changes in mean early‐life conditions influenced males’ relative fertility and lifespan in opposite directions resulting in no overall effect on lifetime reproductive success, suggesting a life‐history trade‐off. In Figure , we use a simple graphical model (adapted from Saeki, Tuda, & Crowley, ) to illustrate these different effects of the variability and mean early‐life conditions. Unlike in males, females’ early‐life ecological conditions had almost no effect on patterns of survival and reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, changes in mean early‐life conditions influenced males’ relative fertility and lifespan in opposite directions resulting in no overall effect on lifetime reproductive success, suggesting a life‐history trade‐off. In Figure , we use a simple graphical model (adapted from Saeki, Tuda, & Crowley, ) to illustrate these different effects of the variability and mean early‐life conditions. Unlike in males, females’ early‐life ecological conditions had almost no effect on patterns of survival and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Graphical illustration of the hypothesized effect of changes in the (a) variability and (b) mean of early‐life rainfall on life‐history trade‐off and allocation patterns (after Saeki et al., ). The thin gray lines represent fitness isoclines along which all positions return an equal payoff.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that different forms of trade-off reproduce different diversity and coexistence patterns ( Levins, 1968 ; Maharjan et al, 2013 ; Kasada et al, 2014 ; Ehrlich et al, 2017 ). The shape of trade-off is determined by various factors like quantitative relationship between resource allocations in life-histories ( Saeki et al, 2014 ), physiological mechanisms ( Bourg et al, 2017 ), and environment ( Jessup and Bohannan, 2008 ). In this study, to implement a trade-off between reproduction and competitive ability with a variable form, we used a function with one shape parameter : where is the trait vector of strain .…”
Section: Species and Strainsmentioning
confidence: 99%
“…From an evolutionary perspective, this issue has been largely debated within the context of germ-soma differentiation (Michod et al 2006;Leslie et al 2017), and also discussed within the context of the evolution of multicellularity (Gavrilets 2010;Ispolatov et al 2012;Amado and Campos 2017;Amado et al 2018). A central feature about the tradeoffs is their structure (Jessup and Bohannan 2008;Saeki et al 2014). Within an ecological viewpoint, the role of the shape of tradeoffs has been related to the emergence of specialists and/or generalists individuals (Egas et al 2004;Guillaume and Otto 2012), to the levels of biodiversity within communities (Farahpour et al 2018), and even to their responses to ecological competition (Maharjan et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Within an ecological viewpoint, the role of the shape of tradeoffs has been related to the emergence of specialists and/or generalists individuals (Egas et al 2004;Guillaume and Otto 2012), to the levels of biodiversity within communities (Farahpour et al 2018), and even to their responses to ecological competition (Maharjan et al 2013). The most diverse forms of tradeoff have been reported, particularly some of those describing relationships between life-history traits are well established in the literature (Jessup and Bohannan 2008;Saeki et al 2014). Nevertheless, the usual approach to describe the tradeoff as single curves relating any two traits that are implicitly subject to biological and biophysical constraints is no longer suitable in case those traits are mediated by other mechanisms or traits.…”
Section: Discussionmentioning
confidence: 99%